Medico-legal aspects of emergency surgery - Henderson, Eduardo; Müller, Augusto; Szafir, Dora; Borrelli, Daniel; Montano, Pedro; Berro, Guido (Cirugía del Uruguay, 2002)
Doctors in general and surgeons in particular we are faced with more and more frequency to situations in which they may legal responsibilities arise during the exercise of the medical act. These situations acquire a very special look when decisions are taken in urgent circumstances or emergency, especially when the need arises of a peremptory surgical act